The Making of Teachers in the Age of Migration Critical Perspectives on the Politics of Education for Refugees, Immigrants and Minorities - Proyer, Michelle; Krause, Sabine; Kremsner, Gertraud (Bloomsbury Academic, 2023)
This open access book aims to unravel entrenched hegemonically-induced hindrances and barriers to internationally acquired teaching competencies' recognition processes. With curricula of teacher education - like school curricula - remaining highly affirmative of localized traditions and styles of reasoning, in times of migration movement, teacher education needs to be reframed to become a global issue. The book's contributions cover manifold facets of how the idea of what makes a teacher is being reframed, touching upon theoretical foundations of perceptions of the teaching profession and concrete analyses of measures to bring internationally trained teachers into systems or make them part thereof. Chapters elaborate on how non-local teachers find their way around and are being treated by pointing to what hinders their (successful) re-entry and how other non- or differently-trained personnel receive preferred treatment. Other contributions focus on strategies teachers apply to deal with ever-growing levels of diversity among students. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the University of Innsbruck, Koblenz University and BeeFlip.